Minimal g?-Open and Maximal g?-Closed sets - Subbulakshmi, D. (Mathematical Statistician and Engineering Applications, 2022)
In this paper a new class of sets namely minimal g?-closed set, maximal g?-open set, minimal g?-open set and maximal g?-closed set and their basic properties are studied.